Strong, cohesive leadership must emerge from Cabinet rejig - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
In a commentary, SMU Associate Professor of Law Eugene Tan opined that “a total of 13 ministries having new ministers in two Cabinet reshuffles within a span of nine months is significant” and “these significant moves underscore not only the urgency of leadership renewal and succession, but also the need for certainty and confidence as Singapore transitions to the 4G leadership which will coincide with the post-Covid era”. He highlighted the need for a strong, cohesive leadership to emerge from the Cabinet reshuffle amid these exceptional times, as he believes that “a leadership that can galvanise the people will enable Singapore to emerge stronger”.